Analisis Faktor-Faktor yang Mempengaruhi Motivasi Belajar Siswa: Studi Kasus Eksploitasi Anak dalam Tradisi Budak Ngambek Timah - Muhammad Zikry; Maulina Hendrik; Vika Martahayu (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Learning motivation of elementary school students is influenced not only by individual factors, but also by social and economic conditions that shape children’s daily experiences. In the Bangka Belitung Islands Province, children’s involvement in the Budak Ngambek Timah tradition remains a culturally accepted practice and poses a serious challenge to educational continuity. This study aims to analyze the factors affecting elementary school students’ learning motivation within the context of child exploitation in the Budak Ngambek Timah tradition. The research employed a qualitative explanatory approach using a case study strategy conducted in Baskarabakti Village, Central Bangka Regency. Data were collected through in-depth interviews, field observations, and document analysis. Informants were selected using purposive and snowball sampling techniques, involving students, parents, teachers, and community members. Data analysis was carried out using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing, with data validity ensured through source and method triangulation. The findings reveal that students’ low learning motivation is influenced by three main factors: economic, social, and physical-health factors. Economic pressure encourages children’s involvement in tin mining activities, reducing their time and energy for learning. Social normalization of child labor positions schooling as a secondary priority, while physical fatigue and health problems resulting from mining activities negatively affect students’ concentration and learning readiness. These findings indicate that low learning motivation is a structural issue that requires collaborative efforts to protect children’s educational rights.